2019
DOI: 10.1038/s41598-018-37972-y
|View full text |Cite
|
Sign up to set email alerts
|

High doses of synthetic antioxidants induce premature senescence in cultivated mesenchymal stem cells

Abstract: Stress-induced premature senescence program is known to be activated in cells by various genotoxic stressors, and oxidative stress is considered to be the main of those. To this end, many studies discover antioxidants as protective anti-aging agents. In the current study, we examined the effects of different antioxidants (Tempol, resveratrol, NAC, DPI) on the mesenchymal stem cells maintained in normal physiological conditions. We used high, but non-cytotoxic antioxidant doses which are widely used in laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(79 citation statements)
references
References 60 publications
(63 reference statements)
7
71
0
1
Order By: Relevance
“…RE also decreased the viability of 3T6 fibroblasts and HL60 tumor cells [165]. In mesenchymal stem cells, 0.1 µM RE promoted self-renewal, whereas concentrations above 5 mM increased senescence rate and inhibited self-renewal [166,167]. As such, further studies are needed to assert the safety of RE against normal healthy cell lines, especially before promoting RE as an anti-cancer agent.…”
Section: Resveratrol Chemotherapeutic Doses Are Cytotoxic To Normal Hmentioning
confidence: 99%
“…RE also decreased the viability of 3T6 fibroblasts and HL60 tumor cells [165]. In mesenchymal stem cells, 0.1 µM RE promoted self-renewal, whereas concentrations above 5 mM increased senescence rate and inhibited self-renewal [166,167]. As such, further studies are needed to assert the safety of RE against normal healthy cell lines, especially before promoting RE as an anti-cancer agent.…”
Section: Resveratrol Chemotherapeutic Doses Are Cytotoxic To Normal Hmentioning
confidence: 99%
“…The treatment of MSCs with antioxidants found to ameliorate the therapeutic potential of MSCs in various disease models [57,58]. In contrast, it has been reported that high but non-toxic doses of antioxidants, when subjected to the proliferating MSCs, can cause DNA damage and induce premature senescence [59]. Therefore, it is also very important to assess or consider the possible detrimental effects such as extracellular H 2 O 2 generated by SOD3 which has been reported to induce angiogenesis by promoting endothelial cell proliferation and migration [60] and stimulates various redox signaling which is involved in pathological conditions by Fenton type reaction and peroxidase activity.…”
Section: Resultsmentioning
confidence: 99%
“…The application of resveratrol to mesenchymal stem cell-based regenerative medicine has been demonstrated in various in vitro bioactivities, including self-renewal, multipotency (33), senescence (21), cell aging (34), osteogenic differentiation (35), adipogenic differentiation (36), and neuronal differentiation (12). Moreover, resveratrol has an e ciently therapeutic effect on in vivo models, including enhancing liver regeneration (37), cardiogenic differentiation in cardiomyopathy (38).…”
Section: Discussionmentioning
confidence: 99%